Coefficients for Active Transport and Thermogenesis of Ca(2+)-ATPase Isoforms - Kjelstrup, Signe (The Biophysical Society, 2009)
Coefficients for active transport of ions and heat in vesicles with Ca(2+)-ATPase from sarcoplasmic reticulum are defined in terms of a newly proposed thermodynamic theory and calculated using experiments reported in the literature. The coefficients characterize in a quantitative manner different performances of the enzyme isoforms. Four enzyme isoforms are examined, namely from white and red muscle tissue, from blood platelets, and from brown adipose mitochondria. The results indicate that the isoforms have a somewhat specialized function. White muscle tissue and brown adipose tissue have the same active transport coefficient ratio, but the activity level of the enzyme in white muscle is higher than in brown adipose tissue. The thermogenesis ratio is high in both white muscle and brown adipose tissue, in agreement with a specific role in nonshivering thermogenesis. Other isoforms do not have this ability to generate heat. A calcium-dependence of the coefficients is found, which can be understood as being in accordance with the role of this ion as a messenger in muscle contraction as well as in thermogenesis. The investigation points to new experiments related to structure as well as to function of the isoforms.